Cadet Perceptions of Military and Civilian Ideology: A Research Note. (January 2013) - Sondheimer, Rachel Milstein; Toner, Kevin; Wilson, Isaiah
Evidence of an actual or perceived gap in ideological beliefs between civilian and military communities informs current debates on the military and its relationship to broader society. The authors examine one cohort of the military and its members' perception of their own ideology in relation to their civilian counterparts using a 2009 survey of cadets at the United States Military Academy. The authors ascertain cadet perceptions of (1) cadet ideological leanings on individual and aggregate levels, (2) the ideological leanings of the civilian population, and (3) the civilian population's assessment of the military's ideological leanings. The authors attempt to discern whether or not this military subpopulation perceives itself as different from the rest of society. The authors find that while members of the Army's future officer corps perceive themselves as more conservative than their civilian peers and society writ large, as a group they hold rather moderate political views.